Global Sustainability Reporting in the Automotive Industry via the eXtensible Business Reporting Language - Árpád Tóth (AIDIC Servizi S.r.l., 2021)
Sustainability measurement has become one of the most important topics for automotive manufacturers. The financial reporting practice has been faced with an increased digitization and standardization process, which was enabled by the either voluntary or required implementation of the eXtensible Business Reporting Language (XBRL) platform. The obligatory adaption appeared in European legislation, which covers both financial, and non-financial information. In the current study, we have made a comparison of the most significant European and American automakers' sustainability reports data content to utilize the sustainability XBRL taxonomy adaptation. Using literature, the development of disclosure requirements was reviewed, following which the adaptation to global sustainability standards (GRI, SASB) in reporting was examined from a qualitative point of view, using a text mining methodology. It has been concluded that by the biggest automotive manufacturers the conditions are currently met to a limited extent, but the most significant obstacle is the lack of linking sustainability information to financial impacts. If the financial regulations require OEMs to adapt, and potentially disclose negative information (such as pollution data, penalties) may negatively affect investor perception. Based on the review XBRL is capable to become a global standard, however, reported contents should be carefully audited and linked to objectively verifiable financial data to provide relevant information to investors, decision-makers.